Análise do comportamento das temperaturas máxima e mínima médias mensais para o estado do Rio Grande do Sul - João, Milena Machado da Luz (2009)
A study has been done on the minimum and maximum temperature monthly averages in the State of Rio Grande do Sul, between 1918 and 2007. Data have been used collected in 10 meteorological stations spread all over the State territory. In a first stage, it has been verified a tendency of these variables in the months of February, May, August and November, throughout the 90 years, and then in periods of 30 years. Right after, mathematical models have been built to refer minimum and maximum temperature monthly averages, for some chosen meteorological stations. For that goal, harmonic analysis technique has been applied for the identification of existing harmonics and their importance in the composition of the models for each station. Data corresponding to an 85-year period, from 1918 to 2002, have been used for the harmonic analysis and composition of the models; and a 5-year period, from 2003 to 2007, for the estimates of theses variables. The results have shown that the more significant positive trends, for the total period of 90 years, have occurred in the minimum temperatures, which have increased remarkably in the State Northern region, while the maximum temperatures have presented negative trends, except in August (winter month). The analysis made for 30-year periods made possible to verify that a constant linear trend does not exist, once intervals have been noticed with a change in the signal of the trend. The estimated values by the mathematical models, proposed for the harmonic analysis technique, have been compared to new sets of observations. The analyses carried through have indicated a good performance of the models as a forecast for the minimum and maximum temperature average variations, taking into account the climatic characteristics of the studied region.